A fuzzy rule-based approach for modelling effects of bench-scale microwave pre-treatment on solubilisation and anaerobic digestion of secondary sludge. (1st January 2014) - Saha, Mithun; Eskicioglu, Cigdem; Sadiq, Rehan
Fuzzy rule-based models were proposed in order to predict the effect of microwave pretreatment on the waste activated sludge (WAS) solubility and anaerobic digestibility or biogas production. The developed models were trained and validated using the experimental data from two separate multilevel factorial designs, containing 24 solubilisation and 54 biogas production runs from batch mesophilic (33 ± 2ºC) digesters. Input parameters were microwave temperature, microwave intensity, WAS concentration and volume percentage of WAS pretreated. Both fuzzy models reasonably predicted the responses, i.e., WAS solubilisation and biogas production with coefficients of determination (R 2 ) of 0.81 and 0.98, respectively. The sensitivity analysis based on rank correlation coefficients indicated that microwave temperature was the most significant parameter for both response variables. The microwave intensity was found not to be a significant factor (<1% contribution) in the biogas production, which is in full agreement with the previously developed regression models.